Rheology and fluid dynamics properties of sugarcane juice - Astolfi-Filho, Zailer [UNESP]; Telis, Vânia Regina Nicoletti [UNESP]; de Oliveira, Eduardo Basilio; Coimbra, Jane Sélia dos Reis; Telis-Romero, Javier [UNESP] (Elsevier, 2011)
The sugarcane juice is a relatively low-cost agricultural resource, abundant in South Asia, Central America and Brazil, with vast applications in producing ethanol biofuel. In that way, a good knowledge of the rheological properties of this raw material is of crucial importance when designing and optimizing unit operations involved in its processing. In this work, the rheological behavior of untreated (USCJ, 17.9 °Brix), clarified (CSCJ, 18.2 °Brix) and mixed (MSCJ, 18.0 °Brix) sugarcane juices was studied at the temperature range from 277K to 373K, using a cone-and-plate viscometer. These fluids were found to present a Newtonian behavior and their flow curves were well-fitted by the viscosity Newtonian model. Viscosity values lied within the range 5.0×10 -3Pas to 0.04×10 -3Pas in the considered temperature interval. The dependence of the viscosity on the temperature was also successfully modeled through an Arrhenius-type equation. In addition to the dynamic viscosity, experimental values of pressure loss in tube flow were used to calculate friction factors. The good agreement between predicted and measured values confirmed the reliability of the proposed equations for describing the flow behavior of the clarified and untreated sugarcane juices. © 2010 Elsevier B.V.
Keywords: Bioprocess; Ethanol; Friction factor; Rheological properties; Sugarcane; Temperature; Agricultural resources; Arrhenius-type equation; Bioprocesses; Central America; Cone and plate; Dynamic viscosities; Experimental values; Flow behaviors; Flow curves; Friction factors; Newtonian behavior; Newtonian model; Pressure loss; Rheological behaviors; Rheological property; South Asia; Temperature intervals; Temperature range; Tube flow; Unit operation; Viscosity value; Fluid dynamics; Forestry; Friction; Tribology; Viscosity; Welding electrodes; Rheology; chemical composition; computational fluid dynamics; flow kinetics; friction; fruit juice; priority journal; reliability; sugarcane; temperature; viscometry; viscosity